Evaluation of the cardiac amyloidosis clinical pathway implementation: a real-world experience. Issue 2 (24th February 2022) - Brons, Maaike; Muller, Steven A; Rutten, Frans H; van der Meer, Manon G; Vrancken, Alexander F J E; Minnema, Monique C; Baas, Annette F; Asselbergs, Folkert W; Oerlemans, Marish I F J
Abstract: Aims: The aim of this study is to evaluate the implementation of the cardiac amyloidosis (CA) clinical pathway on awareness among referring cardiologists, diagnostic delay, and severity of CA at diagnosis. Methods and results: Patients with CA were retrospectively included in this study and divided into two periods: pre-implementation of the CA clinical pathway (2007–18; T1) and post-implementation (2019–20; T2). Patients' and disease characteristics were extracted from electronic health records and compared. In total, 113 patients (mean age 67.8 ± 8.5 years, 26% female) were diagnosed with CA [T1 (2007–18): 56; T2 (2019–20): 57]. The number of CA diagnoses per year has increased over time. Reasons for referral changed over time, with increased awareness of right ventricular hypertrophy (9% in T1 vs. 36% in T2) and unexplained heart failure with preserved ejection fraction (22% in T1 vs. 38% in T2). Comparing T1 with T2, the diagnostic delay also improved (14 vs. 8 months, P < 0.01), New York Heart Association Class III (45% vs. 23%, P = 0.03), and advanced CA stage (MAYO/Gillmore Stage III/IV; 61% vs. 33%, P ≤ 0.01) at time of diagnosis decreased. Conclusion: After implementation of the CA clinical pathway, the awareness among referring cardiologists improved, diagnostic delay was decreased, and patients had less severe CA at diagnosis. Further studies are warranted to assess the prognostic impact of CA clinical pathway implementation.